La coherencia de políticas para el desarrollo en España: desafíos, percepciones, intereses y resistencias institucionales - Millán Acevedo, Natalia (Revista Iberoamericana de Estudios de Desarrollo)
From a human development perspective, government policy should be to ensuring the free exercise of Human Rights for all citizens. Furthermore, governments must consider that those rights should not be restricted or limited by individual’s nationality. In this context, Policy Coherence for Development (PCD) acquires a fundamental importance. This article aims at analyzing the PCD agenda in Spain and the bureaucratic resistance to this agenda within the Spanish Government. The article concludes that the problem of PCD in Spain refers more related to some actors ´s private interests than to a confrontation between local and foreign the Human Rights, at it is sometimes stated by official authorities